How commercial fishing effort is managed. Issue 2 (2nd December 2018) - Anderson, Christopher M.; Krigbaum, Melissa J.; Arostegui, Martin C.; Feddern, Megan L.; Koehn, John Zachary; Kuriyama, Peter T.; Morrisett, Christina; Allen Akselrud, Caitlin I.; Davis, Melanie J.; Fiamengo, Courtney; Fuller, Ava; Lee, Qi; et al.
Abstract: Wild capture fisheries produce 90 million tonnes of food each year and have the potential to provide sustainable livelihoods for nearly 40 million people around the world (http://www.fao.org/3/a-i5555e.pdf ). After decades of overfishing since industrialization, many global fish stocks have recovered, a change brought about through effective management. We provide a synthetic overview of three approaches that managers use to sustain stocks: regulating catch and fishing mortality, regulating effort and regulating spatial access. Within each of these approaches, we describe common restrictions, how they alter incentives to change fishing behaviour, and the resultant ecological, economic and community‐level outcomes. For each approach, we present prominent case‐studies that illustrate behaviour and the corresponding performance. These case‐studies show that sustaining target stocks requires a hard limit on fishing mortality under most conditions, but that additional measures are required to generate economic benefits. Different systems for allocation allow stakeholder communities to strike a locally acceptable balance between profitability and employment.